La autobiografía como estrategia pedagógica para la enseñanza del español en estudiantes Embera en contexto de ciudad (2023)
This document presents the proposal of a didactic material with purpose to contribute and improve the communicative competence of reading and writing in Embera, Chamí, and Katíos indigenous students, who attend the educational institution Restrepo Millán, D, cycle 3, in the back-to-school inclusion program. From the exercise of professional practice, it is evident that the level of reading comprehension in Spanish is low, which leads to a very limited writing, generating frustration in students.